Analisis Perbandingan Kurikulum 2013 dan Kurikulum Merdeka terhadap Pembentukan Moralitas Generasi Z dalam Konteks Pendidikan Nasional - Natasya Victoria; Meriah Charolin Br Sihombing; Leony Br siburian; Indah Rekha Sari; Ruli Pratiwi Deli sirait; Ahmia Br pelawi; Herlina Jasa Putri Harahap (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
Growing up in the digital era, Generation Z has unique characteristics, but faces significant moral issues. The curriculum as an educational tool plays an important role in shaping the character values for this generation. The aim of this research is to analyze and compare the strengths of the 2013 curriculum with the strengths of the independent curriculum in the formation of morality in Generation Z. To achieve this goal, a descriptive qualitative approach to conduct literature research, including studies into political documents, educational theories, and scientific articles, was used. The analysis results show that the 2013 curriculum emphasizes moral values through a scientific approach and character education enhancement (PPK). Meanwhile, the independent curriculum is more flexible and project-based, while the Pancasila student profile promotes contextual learning. Both can shape students' morality, but collaboration among them may be better for education.